Kinos food industries / Zyed Hamidi Zainal Abidin - Zainal Abidin, Zyed Hamidi (2022)
Kinos Food industries was incorporated in 1981 and was located at Pasir Gudang, Johor. This company produces a wide assorted range of snack confectionery under an assortment of iconic household names such as Tora, ding dang, jojo and nini. These product were very popular among children of that generation and even today adults are able to instantly recognise these famous brand names from their chilhood.